Aedes FADD: A novel death domain-containing protein required for antibacterial immunity in the yellow fever mosquito, Aedes aegypti - Cooper, Dawn M.; Chamberlain, Ciara M.; Lowenberger, Carl (Insect biochemistry and molecular biology, 2009)
Microbial infections in insects activate a series of immune responses that culminate in the production of antimicrobial peptides (AMPs). In Drosophila, two signaling pathways, govern the challenge-dependent expression of AMPs; the Toll and IMD pathways. While AMPs have been the subject of much research in mosquitoes, the regulation of the pathways required for AMP expression remains largely unknown. We report here the identification of Aedes FADD (AeFADD), a death domain protein in Aedes aegypti. AeFadd is expressed in all immune-competent tissues and all developmental stages examined. At the transcriptional level, AeFadd transcripts increased when challenged with Escherichia coli but not Micrococcus luteus. In both cases, we observed the induction of two AMP genes; cecropin and defensin. Loss of AeFadd function by dsRNA interference impaired the inducible expression of both AMPs, and rendered adult mosquitoes susceptible to both types of bacteria. Identifying molecules that regulate mosquito immunity may help elucidate the factors that contribute to the vectorial capacity and provide insights into general mechanisms that regulate innate immunity.